Varicocele: An Endocrinological Perspective - Bellastella, Giuseppe; Carotenuto, Raffaela; Caiazzo, Francesco; Longo, Miriam; Cirillo, Paolo; Scappaticcio, Lorenzo; Carbone, Carla; Arcaniolo, Davide; Maiorino, Maria Ida; Esposito, Katherine (Frontiers in Reproductive Health, 2022)
Varicocele affects 15% of the general male population but it is more often identified in patients seeking medical attention for infertility. The adverse effects of varicocele on spermatogenesis are known, but the relation between clinical varicocele and impaired hormonal production is not clear. In published literature there are studies regarding hormonal alterations in patients with varicocele but no review in which all the hormonal findings are explained. The aim of this review is to evaluate, by most common search engine, what is known about hormonal alterations in varicocele-bearing patients, to verify if a cause-effect relationships are documented and to give a useful contribute in clinical management of this kind of patients. We found contradictory results about hormonal status from literature. Some studies showed a reduction of testosterone levels and higher FSH and LH levels that normalize after varicocelectomy, other found lower than normal levels of dihydrotestosterone due to decreased activity of epididymal 5-α-reductase. Lower circulating Anti-Müllerian Hormone levels, accompanied by a decreased Inhibin-B level, were reported as indicators of the decreased Sertoli cells function in varicocele-bearing adult patients. There is no doubt that varicocele could led to hormonal alterations. This review suggests that the altered free sex steroid levels are the result of a defect in the testes of men with varicocele but other studies remain mandatory to ascertain the hormonal features of patients with varicocele and to assess the utility of hormonal evaluation for establishing the duration of varicocele and for better identifying those patients who need surgical correction.